Effect of semi-purified constituent from Guaraná seeds [Paullinia cupana var. sorbilis (Mart.) Ducke] on performance of rats in elevated T maze - Roncon, Camila Marroni (2009)
The purpose of this study was to investigate the effects of chronic administration by gavage of the semi-purified constituent (EPA; 4, 8, or 16 mg/kg) of Paullinia cupana (guaraná) seeds in rats submitted to the elevated T maze (ETM) model of generalized anxiety and panic disorders. The selective serotonin (5-HT) reuptake inhibitor (SSRI, 5-HT), paroxetine (3 mg/kg), was used as a positive control. To evaluate the possible involvement of serotonergic and dopaminergic neurotransmissions in the effects of the EPA on ETM, ineffective doses of metergoline (5-HT2A/2C antagonist receptor) or sulpiride (dopaminergic receptor antagonist), were administered acutely by the intraperitoneal route together with the EPA or paroxetine. The locomotion of the rats was assessed in a circular arena following each drug treatment. EPA (8 and 16 mg/kg) or paroxetine (3 mg/kg) increased the one way-escape latency from the open arm in the ETM, indicative of a panicolytic effect compared to their control group. Metergoline, in the higher dose (1, 2, and 3 mg/kg), but not of sulpiride (10, 20, and 40 mg/kg) produced a panicolytic effect in ETM. The panicolytic effect produced by EPA (8 mg/kg) was blocked by both metergoline (2 mg/kg) and sulpiride (20 mg/kg), whereas the panicolytic effect produced by paroxetine (3 mg/kg) was blocked only by metergoline (2 mg/kg) in the ETM. These results showed that chronic treatment with EPA produced a panicolytic effect in the ETM, and that the dopaminergic and the serotonergic neurotransmission systems are involved in this effect.